An Analysis of Sumbawa Language Shift in Tatebal Village - Septri, Yomi; Supriadin, Supriadin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
This study aims to obtain a types of sumbawa language shift in Sumbawa, especially in Tatebal village. This study uses a descriptive qualitative method which aims to provide an overview of the various types of sumbawa language shift in Sumbawa, especially in Tatebal village. In collecting data, the researcher used direct observation techniques and interviews with Tatebal society. Observation used to know the way of teenagers, adults and old people in Tatebal village during doing a daily conversation. Interviews were conducted with teenagers, adult and old people in the village and interviews with informants,to add information to the research. Based on the research, the sumbawa language shift that occured in Tatebal village very diverse,  for example  the word maming to adress their father became bapak, mambo became sendal, jelaja became jendela etc.